Slurry transport and particle settling in annulus in cuttings reinjection process - Junin, Radzuan; Kong, Wai Meng (Penerbit UTM Press, 2008)
The expending interest in cuttings re-injection process has brought into focus on technical problems relating to the flow and stability properties of suspensions. To design a successful injection program, it is necessary to obtain an optimum delivery efficiency of the cuttings into the formation and the problem of annulus plugging must be avoided. This paper presents the results of a laboratory study to investigate the slurry transport and settling velocity of particles in slurry in vertical annulus. Some aspect of the investigation into the effects of particle size, particle concentration, carrying fluid viscosity and slurry flow rate towards the particle velocity were examined. A criterion for assessing the efficiency of particle transport in slurry in a downward vertical annulus flow, using a relative particle velocity (Vp/Vm) measurement, has been established. The results indicate that the gross effect on particle velocity is similar in both static and dynamic condition. An increase in base fluid viscosity and particle concentration lowers the particle velocity, while a greater particle size increases the particle velocity. A prediction of optimum slurry condition based on results from static and dynamic tests has been done and it shows that slurry with base fluid viscosity of 66.7 cp is needed to achieve the optimum condition in carrying 30% by volume of sand particles with the size of 425 Î¼m - 500 Î¼m into the fractured formation.